2011
DOI: 10.1177/030089161109700115
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p53 Protein and X-ray Repair Cross-Complementing Protein 1 in Non-Small Cell Lung Cancer

Abstract: We found a statistically significant correlation between p53 expression and histopathological tumor type. It is possible that stabilized p53 protein plays an important role in the development of squamous and large cell carcinoma. Our findings also suggest that p53 expression cumulates with the dedifferentiation of cancer cells. It is possible that the expression of XRCC1 is not fixed and could be changed by the status of cancer cells and in relation to therapy. Relevant data about pre- versus post-chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In NSCLC, p53 overexpression significantly correlated with squamous cell carcinoma compared to adenocarcinoma (p = 0.008) and with tumours showing highest grade (p = 0.012). In previous studies, a statistically significant correlation between p53 overexpression and squamous cell carcinoma compared to adenocarcinoma was also reported and, in particular, Rybarova et al found a correlation between p53 overexpression and poorly differentiated tumours in NSCLC [ 15 , 16 ]. Finally, we did not find a significant correlation between positive levels of serum p53Abs and TP53 mutations in the corresponding tumours, nor between TP53 mutations and clinicopathologic features, presumably due to the small number of suitable tumour samples, while a significant correlation between TP53 mutations and tumours with the highest median rate of p53 overexpression was observed within the p53 protein-positive tumour samples (p = 0.04).…”
Section: Discussionmentioning
confidence: 96%
“…In NSCLC, p53 overexpression significantly correlated with squamous cell carcinoma compared to adenocarcinoma (p = 0.008) and with tumours showing highest grade (p = 0.012). In previous studies, a statistically significant correlation between p53 overexpression and squamous cell carcinoma compared to adenocarcinoma was also reported and, in particular, Rybarova et al found a correlation between p53 overexpression and poorly differentiated tumours in NSCLC [ 15 , 16 ]. Finally, we did not find a significant correlation between positive levels of serum p53Abs and TP53 mutations in the corresponding tumours, nor between TP53 mutations and clinicopathologic features, presumably due to the small number of suitable tumour samples, while a significant correlation between TP53 mutations and tumours with the highest median rate of p53 overexpression was observed within the p53 protein-positive tumour samples (p = 0.04).…”
Section: Discussionmentioning
confidence: 96%
“…It also inhibits DNA replication and is a check-point control molecule for progression of the cell cycle. Furthermore, p53 protein is involved in the regulation of apoptosis (53,54). We observed strong p53 nuclear staining in outer cell layer of epithelial cells of Hassall's corpuscles and subcapsular epithelial cells.…”
Section: Thymus and Markers Of Apoptosis (P53 Bcl2 And Survivin)mentioning
confidence: 68%
“…The p53 tumor suppressor gene which shows to be the most frequent target in which their abnormalities plays a significant role in the formation of lung epithelial cell tumors (28). The p53 tumor suppressor gene is set on the human chromosome 17p13 and its product is a nuclear phosphoprotein known as p53.…”
Section: Introductionmentioning
confidence: 99%